2022
DOI: 10.1021/acsaem.2c00646
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline Prussian White Aggregates as a High-Rate and Long-Life Cathode for High-Temperature Sodium-Ion Batteries

Abstract: Cost and resource consideration requires the use of sodium-ion batteries (SIBs) instead of lithium-ion batteries for grid-scale stationary energy storage, which requires a battery to provide high energy density, high power density, and stable cycling over a wide temperature range. Prussian white (PW) is emerging as a potential cathode for SIBs, and the electrochemical properties of PW at room temperature and below have been intensively studied; however, the rapid capacity decay at elevated temperatures still r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…[27] However, they are subjected to internal structural changes and severe Jahn-Teller distortions, due to the Mn-N 6 octahedra experiencing large lattice strain during the uptake and removal of Na + ions. [27][28][29][30] It has also been reported that such monoclinic PW materials suffer from rapid capacity decay and poor reversibility caused by pronounced lattice parameter changes during the phase transitions between monoclinic Na 2 Mn[Fe(CN) 6 ], cubic NaMn[Fe(CN) 6 ] and tetragonal Mn[Fe(CN) 6 ]. [27] Previous efforts to mitigate structural changes and improve stability of PWs mainly focused on partial atom replacements, [31][32][33] removal of interstitial water/vacancies, [34,35] introducing complexing agents, [36][37][38] forming conductive networks [39,40] or designing (cation) defect structures.…”
Section: Introductionmentioning
confidence: 99%
“…[27] However, they are subjected to internal structural changes and severe Jahn-Teller distortions, due to the Mn-N 6 octahedra experiencing large lattice strain during the uptake and removal of Na + ions. [27][28][29][30] It has also been reported that such monoclinic PW materials suffer from rapid capacity decay and poor reversibility caused by pronounced lattice parameter changes during the phase transitions between monoclinic Na 2 Mn[Fe(CN) 6 ], cubic NaMn[Fe(CN) 6 ] and tetragonal Mn[Fe(CN) 6 ]. [27] Previous efforts to mitigate structural changes and improve stability of PWs mainly focused on partial atom replacements, [31][32][33] removal of interstitial water/vacancies, [34,35] introducing complexing agents, [36][37][38] forming conductive networks [39,40] or designing (cation) defect structures.…”
Section: Introductionmentioning
confidence: 99%
“…After activation of three cell cycles at 0.1C, the EIS measurement is further performed to illustrate the influence of the ZnS@CC interlayer on the electrochemical performance of Li–S batteries. It is found that three Nyquist plots consist of a high-frequency semicircle and a low-frequency slope line, which are associated with the charge transfer resistance and the Li + diffusion resistance separately. Apparently, as we can see in Figure d, the semicircle diameters using the ZnS@CC interlayer are smaller than those using the CC interlayer or with no interlayer, proving the significantly enhanced electrochemical kinetics of the sulfur cathode with the ZnS@CC interlayer. Using ZnS@CC as a barrier layer can greatly reduce the charge transfer impedance in the Li–S battery, which is another strong proof of the improvement of the electrochemical dynamics inside the battery.…”
Section: Resultsmentioning
confidence: 89%
“…As for the PW working at elevated temperature, particular attention should be devoted to the fast capacity decay, severe gas production, and serious side reactions, etc., which are mostly caused by the poor stability of electrolyte–electrode interphases . To tackle this issue, a polycrystalline Na 1.81 Fe­[Fe­(CN) 6 ] 0.96 ·2.03H 2 O (Poly-PW) cathode was synthesized by regulating crystal growth (Figure a) . Compared with the conventional monocrystalline PW (Mono-PW), Poly-PW with a lower specific surface-to-volume ratio can lessen the side reactions between the material and the electrolyte at elevated temperature, thus promoting the surface–interface thermodynamic stability (Figure b).…”
Section: Pw For Hot Climatesmentioning
confidence: 99%
“…34 To tackle this issue, a polycrystalline Na 7a). 35 Compared with the conventional monocrystalline PW (Mono-PW), Poly-PW with a lower specific surface-to-volume ratio can lessen the side reactions between the material and the electrolyte at elevated temperature, thus promoting the surface−interface thermodynamic stability (Figure 7b). As a result, Poly-PW exhibits fast and stable Na + storage performance by demonstrating 99 mAh g −1 at 30 C at 50 °C and 77.8% capacity retention over 300 cycles at 70 °C (Figure 7c).…”
Section: Pw For Hot Climatesmentioning
confidence: 99%
See 1 more Smart Citation